The olfactory apparatus in the catfish, Mystus pelusius (Bagridae) - Jasim, Basim M (Indian Journal of Fisheries, 2011)
M. pelusius have a drawn apart tubular anterior and longitudinal posterior nostrils, while it has an ordinary histological structure in its olfactory apparatus. There is a heavy ciliated olfactory chamber and oval rosette. The sensory cells are characterized by lower density (750 cell / 0.1 mm2), but with increased ratio of them in consideration to sustentacular cells (3/2).